2012
DOI: 10.1038/pcan.2012.38
|View full text |Cite
|
Sign up to set email alerts
|

Race is associated with discontinuation of active surveillance of low-risk prostate cancer: Results from the Duke Prostate Center

Abstract: Black race was associated with discontinuation of AS for treatment. This relationship persisted when adjusted for socioeconomic and clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 38 publications
0
57
0
1
Order By: Relevance
“…These disparate findings were derived mainly retrospectively from cohorts with varying sociodemographics, clinical risk, treatment regimens, and follow-up. Among men with PCa managed with AS, AA race has been linked to discontinuation of surveillance followed by active treatment [20]. After RP for all-risk localized disease, AA men have been found to have more adverse pathologic features [21].…”
Section: Discussionmentioning
confidence: 99%
“…These disparate findings were derived mainly retrospectively from cohorts with varying sociodemographics, clinical risk, treatment regimens, and follow-up. Among men with PCa managed with AS, AA race has been linked to discontinuation of surveillance followed by active treatment [20]. After RP for all-risk localized disease, AA men have been found to have more adverse pathologic features [21].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Multiple reports have demonstrated that AA men are more likely to progress to higher-risk disease after enrollment in surveillance. [27][28][29] As such, Sundi et al called into question the generalizability of active surveillance (AS) criteria after showing that 27.3% of AA men who met the AS criteria experienced disease upgrading at RP, a rate nearly twice that of Caucasians. 18 Although multiple factors, including patient preference, are considered in electing AS, PHI may provide helpful information for AA men during counseling.…”
Section: Commentmentioning
confidence: 98%
“…One retrospective study evaluated the effect of race on discontinuation of AS for patients with low-risk PCa. Their results showed that AA men had more aggressive disease and were more likely to progress on AS and proceed to treatment faster than CS men were [27]. A large study on pathologic and FFbF outcomes in very low-risk AA men who qualify for AS but underwent immediate RP showed that AA men had significantly higher rates of upgrading, positive surgical margins, and CAPRA-S score than CS men did [28].…”
Section: Discussionmentioning
confidence: 99%